PERANAN DINAS TENAGA KERJA PROVINSI SUMATERA UTARA DALAM MENINGKATKAN KEWIRAUSAHAAN PRODUKTIF STIMULASI EKONOMI DI KOTA MEDAN - Rizka Hidayati; Nur Fadhilah Ahmad Hasibuan (Universitas Muhammadiyah Metro, 2023)
The purpose of this study is to explain the role of the Human Resources Department of North Sumatra in developing productive entrepreneurship to drive the economy of Medan city. This study uses qualitative research techniques. The data analysis technique in this study is descriptive analysis. This type of research data is primary data. Information gathering techniques in this study were conducted through interviews, mapping, and documentation. The findings show that North Sumatra's human resources department is on track to develop and strengthen. However, North Sumatra's personnel department still faces obstacles in promoting an entrepreneurial economy in Medan city. In other words, there is a lack of trust in entrepreneurs because they don't understand their business and they don't have the funds to develop their own business.